Computed Tomography Guided Biopsy and Gene X-pert MTB/Rif Ultra can be Deceptive in Spondylodiscitis – A Rare Case Report of Hodgkin’s Lymphoma Mimicking Spondylodiscitis - Vyankatesh Deshpande; Abhijit Pawar; Clevio Desouza; Hari Charan Adepu (Journal of Orthopaedic Case Reports)
Introduction: Tuberculosis (TB) is a leading cause of spinal infections, frequently presenting as spondylodiscitis. However, its clinical and radiological features can resemble those of Hodgkin’s Lymphoma (HL). While Gene X-pert MTB/Rif Ultra and computed tomography (CT)-guided biopsies are common diagnostic tools for TB, they may sometimes be inconclusive. In such cases, HL should be considered as a differential diagnosis. Positron emission tomography-CT (PET-CT) scans are useful in assessing whether the disease is metabolically active. Accurate and timely diagnosis is essential for effective treatment, especially when initial tests suggest an infectious cause. Case Report: A 16-year-old male presented with lower back pain radiating to the lower limbs and difficulty walking. Magnetic resonance imaging revealed vertebral body destruction suggestive of spondylodiscitis. Despite anti-tubercular therapy, his condition worsened. Gene X-pert MTB/Rif Ultra and multiple CT-guided biopsies initially suggested a granulomatous lesion but did not confirm TB. Subsequent imaging revealed systemic nodular lesions, raising the suspicion of malignancy. Immunohistochemical studies confirmed HL with positivity for CD15 and CD30. The patient responded positively to chemotherapy and has been in remission for 1 year. Conclusion: This case underscores the diagnostic challenges of distinguishing between spinal TB and HL. Initial tests such as Gene X-pert MTB/Rif Ultra and CT-guided biopsies can sometimes produce false negatives, leading to delays in accurate diagnosis and appropriate treatment. The use of PET-CT and detailed immune-histochemical analysis proved crucial in this case, emphasizing the importance of a comprehensive diagnostic approach when conventional treatments fail. This case contributes to the orthopedic literature by highlighting the need to consider HL in differential diagnoses and the role of advanced imaging and biopsies in ensuring timely and accurate diagnosis.